Migratory trajectory and recomposing of Alpine societies - Thierry Amrein (Revue de Géographie Alpine)
In 2011 and 2012, we carried out a multi-disciplinary field study in the lower Valais region. The goal of this study was to account for the immigration and integration mechanisms at a very local level, as close as possible to the experience of our acting participants, who were immigrants. The project comprised an anthropological section, which led to the content of this article, and a historical part that makes visible the continuities and disruptions of migratory movements.This anthropological research, which essentially has a qualitative nature, comprised two inseparable aspects. On the one hand, we questioned the motivations behind the ever-increasing number of migrants settling over the past two or three decades in 14 villages situated in the Bagnes and Entremont valleys, as well as a commune in the Rhône plain, and the way in which they have managed to become “social actors” and put down roots in their respective communities. On the other hand, our study raises the issue of the perpetual recomposing of mountain societies, still often perceived – or promoted – as entities that are rather homogeneous, authentic and specific. In other words, our survey is situated at the intersection between individual and collective identities.